A contribui????o do movimento no processo de aprendizagem: um olhar sobre a concep????o de educadores - Garcia, Karine Amado (2017)
The objective of this work was to investigate the conception of elementary school teachers in relation to the contribution of the movement in the learning process of their students, presenting the relationships between movement and learning; Highlighting the benefits of movement to enrich the student's cognitive structure and the relevance of play activities in this context; And analyzing the teacher's perspective on such relationships. The study is characterized by the Exploratory Field Research modality and the collection instrument used was an open questionnaire applied to twenty teachers from two schools of the Municipal Network of S??o Paulo. The analysis of the results showed that the conception of learning presented by teachers has two aspects: knowledge acquisition and knowledge construction. In this context, the games were cited as a learning facilitator. On the role of Physical Education in the school environment, teachers assigned two functions: disciplining and development. Finally, all teachers believe in the influence of motor in learning and in the relationship between motor and cognitive development. The justifications varied between learning in the practice of Physical Education classes what was taught in the classroom, Physical Education as a promoter of integral development and discipline, and the use of games and games to stimulate cognitive development. Thus, we conclude that most teachers are aware of the influence of the movement in the learning process, but we suggest that more studies be conducted addressing these issues in order to contribute to the improvement of teaching and learning processes, recognizing the relevance of Physical Education in this aspect.